Prevalence of sleep deprivation and its effect on the performance of family medicine residents in Riyadh, Saudi Arabia - Mohammed A Alrishan; Sulaiman A Alshammari (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: A good night sleep is essential for good health since it supports proper brain functions and its ability to make decisions and to learn and remember new information. The objectives of this study were to assess the prevalence of sleep deprivation (SD) and its effects on the performance of family medicine residents in Riyadh. MATERIALS AND METHODS: A cross-sectional study design was based on an informative-validated self-assessment questionnaire, especially designed by the Medical Council of Canada, to assess the performance of family medicine physicians. Ethical approval was obtained from the institutional review board. Data was analysed using SPSS; initial analysis included computating frequencies and percentages. Odds ratios were calculated for association between. RESULTS: Of the total 258 respondents, 32% had low performance, and 41.5% of the sample suffered from SD, with a male/female ratio of 1:1. There were no significant differences between residency level (R1, R2, R3, and R4) and the average number of sleeping hours. However, 45.5% of R1, 47.8% of R2, 32.4% of R3, and 41.5% of R4 suffered from SD. The data showed a significant difference between the performance and the average number of hours of sleep of the respondents on a typical day. SD was associated with the low performance of 48.6% of subjects compared to 18.3% in those who slept for 7-9 h (aOR=3.96). CONCLUSION: SD negatively affects the performance of family medicine residents. There was no statistically significant difference between males and females in performance. The center for residents' training should consider adequate sleep as essential for the promotion of health and performance.